Maternal Phytosterol Supplementation during Pregnancy and Lactation Modulates Lipid and Lipoprotein Response in Offspring of apoE-Deficient Mice. Issue 8 (17th June 2015) - Rideout, Todd C; Movsesian, Cheryl; Tsai, Yi-Ting; Iqbal, Aadil; Raslawsky, Amy; Patel, Mulchand S
Abstract: Background: In utero exposure to excessive cholesterol has been shown to increase fetal plasma cholesterol concentration and predispose adult offspring to cardiovascular disease (CVD) risk. Because lipid-lowering drugs are contraindicated during pregnancy, natural cholesterol-lowering compounds may be a safe and effective alternative to reduce CVD risk in offspring born to hypercholesterolemic mothers. Objective: This study used the hypercholesterolemic apolipoprotein E–deficient (apoE −/− ) mouse model to test the hypothesis that mothers supplemented with phytosterols during gestation and lactation would produce offspring with a more favorable lipid profile than offspring from unsupplemented mothers, despite having a genetic predisposition toward hypercholesterolemia. Methods: Sixteen female apoE −/− mice were randomly assigned to 2 diets fed throughout the gestation and lactation periods: a cholesterol-enriched diet (CH) (0.15%) or the cholesterol-enriched diet supplemented with phytosterols (CH/PS) (2%). Serum lipids and lipoproteins were measured by enzyme assay and nuclear magnetic resonance spectroscopy, respectively, and liver cholesterol was analyzed by GC. Results: Compared with the CH-fed dams at the end of lactation, phytosterol-supplemented dams displayed lower ( P < 0.05) serum total cholesterol (−55%), non-HDL cholesterol (−56%), and LDL cholesterol (−47%), but no change ( P > 0.05) in HDL cholesterol and triacylglycerol (TG) concentrations. Pups from phytosterol-fed dams demonstrated lower ( P < 0.05) total cholesterol (−25%), non-HDL cholesterol (−25%), LDL cholesterol (−47%), and TGs (−41%), without any change ( P > 0.05) in HDL cholesterol compared with pups from CH-fed dams. Furthermore, compared with pups from CH-fed dams, pups from phytosterol-supplemented dams displayed a lower ( P < 0.05) number of total LDL particles (−34%), VLDL particles (−31%), and HDL particles (−30%). Conclusion: Our results in apoE −/− mice suggest that even under strong genetic predisposition to hypercholesterolemia, pups born to mothers supplemented with phytosterols during gestation and lactation exhibit favorable liver and serum lipid responses compared with pups from unsupplemented mothers.